A comparative analysis of us and Indian laws against phishing attacks. (2022) - Siddiqui, Nafees; Chaudhary, Lokesh; Tripathi, Padmesh; Kumar, Nitendra; Kumar, Santosh
Abstract: Phishing attacks employ websites and email addresses that claim to be from a recognizable and reputable company in order to manipulate people into providing financial or personal data online at the fraudulent sites. Phishing attacks exploit the numerous vulnerabilities that occur in processes and structures as a function of the human element. There are several cyber-attacks that use multiple techniques or approaches to propagate. They take advantage of the flaws identified in end users, rendering the users the most vulnerable part in terms of protection. The phishing issue is vast, and there is no one solution that can easily address all of the current fatal flaws.